2021
DOI: 10.1002/lary.29423
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐Life Practice Patterns in Head and Neck Cancer

Abstract: Objective/Hypothesis: Despite the importance of symptom management and end-of-life (EOL) care in head and neck cancers (HNC), there is little literature on care practices in this population. This study examines EOL care practice patterns using nationally established metrics.Study Design: Retrospective chart review. Methods: Review of HNC patients who were actively followed and treated (defined as one clinic note within 90 days, two within preceding 9 months, and having received treatment at our institution) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…Studies of head and neck cancer patients demonstrate differences in the understanding and interpretation of information between healthcare professionals, patients and carers, alongside differences in preferences regarding openness to prognostic discussions. 585 Whilst acknowledging that there will be differences in the desire to discuss the future, the opportunity for such a discussion may affect patients' access to palliative care and hospice care at the end of life. 586 There are many different models that support discussions relating to advance care planning; these can be helpful frameworks to support clinicians when initiating conversations.…”
Section: Complex Wound Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of head and neck cancer patients demonstrate differences in the understanding and interpretation of information between healthcare professionals, patients and carers, alongside differences in preferences regarding openness to prognostic discussions. 585 Whilst acknowledging that there will be differences in the desire to discuss the future, the opportunity for such a discussion may affect patients' access to palliative care and hospice care at the end of life. 586 There are many different models that support discussions relating to advance care planning; these can be helpful frameworks to support clinicians when initiating conversations.…”
Section: Complex Wound Managementmentioning
confidence: 99%
“…Advance care planning should be considered to support options for care, including the continuation of further lines of therapy, alongside less interventional approaches and end-of-life care planning. 585 Importantly, advance care planning may not reduce hospital attendance for patients with head and neck cancer, as has been anticipated in patients with other conditions; rather, the difficulty of managing symptoms such as bleeding, airway obstruction and complex wounds in the home setting frequently necessitates hospital-based care. Crucial to introducing advance care planning into practice is the recognition of key ‘triggers’ that prompt the clinician to consider and raise conversations regarding such planning (Table 19).…”
Section: Advance Care Planning and End-of-life Carementioning
confidence: 99%
“…While the incorporation of mAB therapy into advanced oncologic care has been suggested to delay advanced care planning and use of palliative care services for patients and their families, there is no literature to date, to the best of our knowledge, on the effects of mAB therapy on end‐of‐life health care utilization and costs for patients with HNC 5 . Prior studies have demonstrated that HNC patients with late hospice enrollment have increased health care spending in the last 30 days of life 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 While the incorporation of mAB therapy into advanced oncologic care has been suggested to delay advanced care planning and use of palliative care services for patients and their families, there is no literature to date, to the best of our knowledge, on the effects of mAB therapy on end-of-life health care utilization and costs for patients with HNC. 5 Prior studies have demonstrated that HNC patients with late hospice enrollment have increased health care spending in the last 30 days of life. [5][6][7] Despite support for early advanced care planning, the expanding landscape of mAB therapy has further added to the complexity of decision-making regarding early integration of palliative care services and possible timing of mAB treatment withdrawal.…”
mentioning
confidence: 99%
See 1 more Smart Citation